Behavior of energy multinationals and the fight against environmental pollution in Latin America during the period 2011-2022 - Merma Paz, Valeria; Alva Soto, María José De Lucía; Melgar Alvarado, Luis Fernando; Soto Montalvo, Yadira Milagros; Quispe Valderrama, Juan Daniel; Moscoso Cuaresma, Julio Ricardo; Jauregui Arroyo, Ralphi Ricardo (LACCEI, 2024)
The study of the behavior of multinational companies in the energy sector has sparked interest in their dynamic entry into global markets through Foreign Direct Investment (FDI), with Latin America being one of the regions experiencing high flows due to its comparative resource advantages. Thus, this study aims to determine trends in the behavior of energy multinational corporations and the fight against environmental pollution during the period from 2011 to 2022. The methodology of systematic literature review using Scopus and ScienceDirect search engines was used for this purpose. Among the results, it was found that the mixed approach is predominant over qualitative or quantitative; moreover, inquiries mainly focus on the study of multinational companies. Additionally, when grouping the research, trends in the behavior of energy multinational corporations tend to yield different results among countries due to the influence of mechanisms and policies that define the performance of FDI in economic, social, and environmental pillars. In conclusion, it is suggested to cover the evolutionary trends of the performance of energy multinational corporations, employing comparative analyses between regions, compliance with Sustainable Development Goals, and quantitative analyses of technologies used in the sector.